Optimization process of partially cooked corn grits (PCCG) by response surface methodology - Sari, Anjar Ruspita; Abdul Rahman, Russly; Shukri, Radhiah; Hussain, Norhayati (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Corn is used as a staple food to substitute rice by processing it into steamed corn grits, especially in Central Java and Madura region, Indonesia. However, the traditional preparation is time consuming as it takes 3-4 days. The objective of this study is to identify the optimum particle size (0.3-1.4mm), initial moisture content (40-60%) and temperature (115-126°C) during processing with respect to the quality of corn grits using response surface methodology (RSM). Yellowness index (YI), resistant starch (RS) and resilience were used as responses because they had high R2 (0.92, 0.94 and 0.97 respectively). The results indicated that particle size and initial moisture content contributed significantly (p<0.05) on YI, water absorption index (WAI) and water solubility index (WSI). Moreover, temperature significantly (p<0.05) affected the RS. The optimum processing conditions for particle size, initial moisture content and temperature were 0.30 mm, 52.33 % and 123.67°C with 0.93 of overall desirability. The optimum processing conditions had a shorter preparation time of PCCG which is less than a day.